Endoglin (CD105) and proliferation index in recurrent glioblastoma treated with anti-angiogenic therapy - Bastos, António G. P.; Carvalho, Bruno; Silva, Roberto; Leitão, Dina; Linhares, Paulo; Vaz, Rui; Lima, Jorge (Frontiers in Oncology, 2022)
CD105 is an angiogenic biomarker that is useful to determine the microvessel density (MVD) within a tumour, namely in highly vascularized tumour like glioblastoma (GBM). However, its expression has shown inconsistent associations with the prognosis of GBM patients. The aim of this study was to evaluate the value of MVD-CD105 (microvessel density assessed with anti-CD105 antibody) and Ki-67 (proliferation index marker) as prognostic and therapy response biomarkers, specifically in primary tumors and in recurrent tumoral specimens of a cohort of GBM patients, treated with bevacizumab upon recurrency. We conducted a retrospective study of 102 consecutive GBM patients treated with bevacizumab upon recurrence at CHUSJ between 2010 and 2017. Demographic, clinical and survival data of all patients were collected and analysed. Tissue expression of MVD-CD105 and Ki-67 in primary and recurrent specimens was correlated with progression-free survival after temozolomide (PFS-1), progression-free survival after bevacizumab (PFS-2) and overall survival (OS). The immunohistochemical expression score for MVD-CD105 was similar in primary and recurrent tumoral specimens (mean score of 15 and 16, respectively). Likewise, the mean Ki-67 expression was similar in primary (mean of 31% tumour cells) and recurrent tumoral specimens (mean of 29% tumour cells). MVD-CD105 expression in primary tumours had no impact in PFS1, PFS2 or OS. At recurrence, patients whose tumours showed increased MVD-CD105 had worse median PFS-2 (2 months vs 8 months; p=0,045) and OS (17 months vs 26 months; p=0,007) compared to those whose tumours showed lower MVD-CD105. CD105 tumoral pattern and localization had no impact on prognosis. Ki-67 expression was not associated with differences in survival outcomes. In this study, higher MVD-CD105 expression in recurrent GBM patients seems to be associated with a worse PFS-2 and OS, while portending no prognostic significance in the primary tumours. This highlights the importance of keeping track of the molecular evolution of the tumour over the course of the disease.